Beca as Bricoleur: How Pitch Perfect Embraces the New College Composer. - Howard, K. Shannon (Studies in Popular Culture)
The article offers the author's insights regarding the benefits offered by digital technologies on college composition focusing on the relation of college composition on the film "Pitch Perfect." The author mentions that characters of the film such as Beca Mitchell show that authentic bricolage as practice does not always present digital culture. He discusses the role of bricoleur such as Mitchell and in the book "The Savage Mind," by Claude Levi-Strauss.